Harmonization of Effective Learning Hour Policies and the National Curriculum: Strategies to Overcome Bureaucratic Rigidity in Strengthening Cross-Sectoral Synergy - Mahmud Ladede (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This research is driven by the urgent issue of rigidity in effective learning hour policies and the national curriculum, which creates conflicting program priorities and discrepancies in academic calendars, resulting in weak cross-sectoral synergy between the Ministry of Religious Affairs and the Department of Education. This condition poses a serious obstacle for Islamic Religious Extension Officers in fulfilling their strategic role within formal educational institutions to mitigate the moral degradation of adolescents. Utilizing a descriptive qualitative research method with a public policy analysis approach based on William N. Dunn’s model, this study evaluates various regulatory alternatives capable of bridging these administrative constraints. The results indicate that policy synchronization at the regional level, such as through Joint Decrees (SKB) on the integration of guidance services, serves as an effective solution to dismantle bureaucratic silos. The discussion emphasizes that flexibility in the academic calendar and the standardization of extension officer competencies are key to building systematic collaboration, ensuring that youth guidance programs can be implemented without disrupting national curriculum targets, thereby facilitating better accessibility and professional effectiveness for Islamic Religious Extension Officers in the field.